Finance, terror, and science on stage: current public concerns in 21st-century British drama - Frank, Kerstin; Lusin, Caroline (Mannheimer Beiträge zur Literatur- und Kulturwissenschaft, 2017)
This collection of essays examines the contribution of British plays to key social, political, and intellectual debates since 2000. It explores some of the most pressing concerns that have dominated the public discourse in Britain in the last decade, focusing on their representation in dramatic texts. Each essay provides an in-depth analysis of one play, assessing its particular contribution to the debate in question. The book aims to show how contemporary drama has developed unique ways to present the complexities and ambiguities of certain issues with aesthetic as well as emotional appeal.